Diseminasi Penggunaan Kompor Biomassa dan Pelet Biomassa pada Kelompok Pelaku Usaha Minuman Serbuk Herbal - Syamsul Ma'arif; Elly Wuryaningtyas Yunitasari; Kusmendar Kusmendar; Shanta Rezkita; Nikma Wahyu Nurdaningsih; Paulina Retno Anjani Sugito; Ricky Novan Pradhana (Unika Santu Paulus Ruteng, 2023)
Rumpoen business group has a business making herbal powder drinks. The business is growing during the pandemic because herbal drinks can increase endurance. However, making herbal powder drinks requires much energy in the crystallization process. High energy needs affect the determination of product prices. As such, alternative technologies are needed to overcome them. The technology is a biomass stove with the principle of gasification technology that can produce higher heat energy than ordinary stoves. The purpose of this community service activity is to introduce biomass stoves as an alternative technology and biomass pellets made from production dregs waste. Activities were carried out through technology dissemination and presentations and ended with discussions, questions, and answers. Then all participants were asked to fill out a questionnaire to evaluate this community service activity. The evaluation results, related to the service activity's purpose, showed a level of 100%, from which the participants knew and understood the use of biomass stoves and the utilization of dregs waste into biomass pellets. However, the participants' interest in implementing the activity results only reached 60%. Overall, the participants stated that the level of satisfaction with community service activities was 4.8 out of a scale of 5. The participants hoped for more intensive service activities, additional training, and additional equipment assistance.